ACCURACY OF MILK YIELD ESTIMATION IN DAIRY CATTLE FROM MONTHLY RECORD BY REGRESSION METHOD - Kuswahyuni, I.S.; Kurnianto, E.; Nuringtias, N.L.; Johari, S. (Diponegoro University, 2009)
This experiment was conducted to estimate the actual milk yield and to compare the estimation accuracyof cumulative monthly record to actual milk yield by regression method. Materials used in this experimentwere records relating to milk yield and pedigree. The obtained data were categorized into 2 groups i.e. AgeGroup I (AG I) that was cow calving at < 36 months old as many as 33 cows with 33 lactation records andAG II that cows calving e” 36 months old as many as 44 cows with 105 lactation records. The first three toseven months data were used to estimate actual milk yield. Results showed that mean of milk yield/ head/lactation at AG I (2479.5 ± 461.5 kg) was lower than that of AG II (2989,7 ± 526,8 kg). Estimated milk yieldsfor three to seven months at AG I were 2455.6±419.7; 2455.7±432.9; 2455.5±446.4; 2455.6±450.8; 2455,64± 450,8; 2455,5 ± 459,3 kg respectively, meanwhile at AG II was 2972.3±479.8; 2972.0±497.2; 2972.4±509.6;2972.5±523.6 and 2972.5±535.1 respectively. Correlation coefficients between estimated and actual milkyield at AG I were 0.79; 0.82; 0.86; 0.86 and 0.88, respectively, meanwhile at AG II were 0.65; 0.66; 0.67;0.69 and 0.72 respectively. In conclusion, the mean of estimated milk yield at AG I was lower than AG II.The best record to estimate actual milk yield both at AG I and AG II were the seven cumulative months.